Colloidal Quantum Dots: Synthesis, Composition, Structure, and Emerging Optoelectronic Applications. Issue 3 (27th December 2022) - Zhang, Jian; Zhang, Shaohui; Zhang, Yule; Al‐Hartomy, Omar A.; Wageh, Swelm; Al‐Sehemi, Abdullah G.; Hao, Yabin; Gao, Lingfeng; Wang, Hao; Zhang, Han
Abstract: In recent decades, quantum dots (QDs) with tunable bandgap, large absorption coefficient, high quantum yield, multiexciton effect, and easy solution processing have unparalleled advantages in photoelectric conversion. Optoelectronic devices based on QDs of different composition have made great progress. However, there is still a lack of reviews on comparing the optoelectronic application level of semiconductor quantum dots (SQDs), perovskite quantum dots (PQDs), and carbon quantum dots (CDs), and also rarely providing a comprehensive summary of photocatalysis. First, this review almost completely summarizes advantages and disadvantages of common synthesis methods for QDs, especially pointing out the importance of optimization strategies for preparing high‐quality QDs such as ligand engineering, ion exchange, and purification separation. Then, compositions of SQD, PQD, CD, and corresponding optoelectronic properties are introduced, respectively. Next, the strengths and weaknesses of the four QDs structures are compared in detail. Finally, the flourishing development in various optoelectronic applications is separately demonstrated, and development degree of SQDs, PQDs, and CDs is compared to discover the most suitable application scenarios for each. On these bases, bottlenecks and opportunities are also put forwarded, hoping to stimulate more breakthroughs in this field. Abstract : Quantum dots (QDs) have unparalleled advantages in optoelectronic fields including light‐emitting diode (LED), solar cell (SC), photodetector (PD), laser device (LD), and photocatalysis (PC). However, it's impossible for high performance to separated from excellent synthesis method, reasonable composition selection, and accurate structure design. The review will provide the basis for its high‐quality applications and further expand other applications.